2007
DOI: 10.1186/1471-2474-8-16
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic differentiation potential of adolescent human tendon tissue: an in-vitro cell differentiation study

Abstract: Background: Tendinosis lesions show an increase of glycosaminoglycan amount, calcifications, and lipid accumulation. Therefore, altered cellular differentiation might play a role in the etiology of tendinosis. This study investigates whether adolescent human tendon tissue contains a population of cells with intrinsic differentiation potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
80
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(85 citation statements)
references
References 41 publications
2
80
3
Order By: Relevance
“…Ectopic bone formation in the Achilles tendon after mid-point tenotomy has also been reported to be caused by the direct conversion of tendon tissue to cartilage (Rooney et al, 1993). Other studies also reported the presence of resident progenitor cells with multidifferentiation potential in the tendon (Salingcarnboriboon et al 2003;Bi et al 2007;de Mos et al 2007). Injection of recombinant human bone morphogenetic protein -2 (rhBMP-2) into the tendon increased ectopic bone formation, indicating that the tendon consisted of cells that were responsive to BMP and were capable of differentiating along the chondro-osseous pathway (Hashimoto et al 2007).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Ectopic bone formation in the Achilles tendon after mid-point tenotomy has also been reported to be caused by the direct conversion of tendon tissue to cartilage (Rooney et al, 1993). Other studies also reported the presence of resident progenitor cells with multidifferentiation potential in the tendon (Salingcarnboriboon et al 2003;Bi et al 2007;de Mos et al 2007). Injection of recombinant human bone morphogenetic protein -2 (rhBMP-2) into the tendon increased ectopic bone formation, indicating that the tendon consisted of cells that were responsive to BMP and were capable of differentiating along the chondro-osseous pathway (Hashimoto et al 2007).…”
Section: Discussionmentioning
confidence: 95%
“…Recent studies reported that human and mouse tendons harbored a unique cell population with universal stem cell characteristics (tendon stem/progenitor cells), and they could differentiate into chondrocytes and osteoblasts (Salingcarnboriboon et al 2003;Bi et al 2007;de Mos et al 2007). These isolated tendon stem/progenitor cells could regenerate tendon-like tissues after extended expansion in vitro and transplantation in vivo (Bi et al 2007).…”
mentioning
confidence: 99%
“…Primers were designed using PrimerExpress 2.0 software (Applied Biosystems, Foster City, CA) to meet SYBR 1 Green (TLRs only) or Taqman 1 requirements. BLASTn ensured gene specificity of the following primers: TLR2 (F: 5 0 -CTACTGGGTGGAGAACCTTATGGT-3 0 ; R: 5 0 -CCGCTTATGAAGACACAACTTGA-3 0 ), TLR4 (F: 5 0 -GGCATGCCTGTGCTGAGTT-3 0 ; R: 5 0 -CTGCTACAACAGA-TACTACAAGCACACT-3 0 ), MMP1, MMP3, MMP9, MMP13, 7 and GAPDH 13 as calibrator. For real-time RT-PCR 20 mL samples were prepared containing sample cDNA, forward and reverse primers, and either qPCR TM Mastermix Plus for SYBR 1 Green I (Eurogentec, Nederland B.V., Maastricht, The Netherlands) or TaqMan 1 Universal PCR MasterMix (ABI, Branchburg, NJ), according to the manufacturer's guidelines.…”
Section: Rna Isolation and Real-time Rt-pcrmentioning
confidence: 99%
“…Clinically speaking this would not be a desired outcome and should be avoided, in the same way that miss-expression and differentiation down an inappropriate path could compromise the native tissue properties. Therefore, it would be essential to standardize any genetic modification of cells (although difficult) to limit MSCs sending inappropriate signals to the environment, as has been demonstrated in the laboratory [5].…”
Section: Basic Scientific Researchmentioning
confidence: 99%
“…As the animal grows, cells develop into different types of connective tissue; bone, tendon, cartilage, the lymphatic and circulatory systems [3,4] http://en.wikipedia.org/wiki/Mesenchymecite_note-isbn0-7817-8577-4-2. These cells thrive and survive within the collagen based matrix, which provides feedback to the cells based on architectural configuration, thought to influence certain activity in response to chemical stimuli [5]. As embryology progresses subsets of the mesenchyme will give rise to the bone and cartilaginous framework of the organism as well as the ligaments and tendons which make up the 'soft tissue skeleton'.…”
mentioning
confidence: 99%